PENERAPAN MODEL PROCESS-ORIENTED GUIDED INQUIRY LEARNING (POGIL) PADA PEMBELAJARAN HUKUM NEWTON DI SMP - Syaiful Amri; Tomo Djudin; Hamdani Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
Abstract This study aims to determine the effectiveness of application Process-Oriented Guided Inquiry Learning (POGIL) model to improve student learning outcomes in Newton's Laws subject at class VIII Bawari Islamic Middle School Pontianak. The sample of this study were 20 students of class VIII A. In which selected based on the intact group. The instrument consisted of 10 multiple choice questions and 5 essay questions for each pretest dan posttest. The treatment of this class action was carried out in two meetings, for Newton 1st, 2nd, and 3rd law, assisted by the LKPD which provided in each meeting. From the results of study there was an increase in the average score of students by 25.5 before and after being given treatment. Average score of tudent was increased by 25.5. The results of this study also show that there were significant differences in student learning outcomes, and the effectiveness of using the POGIL model fell into the medium category with an effectiveness value of 0.52. Based on the results of these studies indicate that the application of the POGIL model was effective to improve student learning outcomes in Newton's Laws subject at class VIII Bawari Islamic Middle School Pontianak. Keywords: Learning Outcomes, Newton's Lows Lesson Material, POGIL, Process Oriented Guided Inquiry Learning.